The Limehouse Golem [videorecording (DVD)] - Cooke, Olivia, 1993-; Nighy, Bill, 1949-; Reid, Sam, 1987-; Ackroyd, Peter, 1949- (RLJ Entertainment, 2017)
Lizzie has been accused of murdering her husband, and her death by hanging seems all but inevitable. That is until Detective Inspector John Kildare is assigned to the case of a serial killer who murders innocent victims while leaving his distinctive signature in blood.